2021
DOI: 10.3390/w13020181
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Fate of Emerging Pollutants in Water Environment and Options for Their Removal

Abstract: Emerging pollutants (EPs) are chemicals known to cause major impacts on the terrestrial, aquatic life and human health as a result of their chronic and acute toxicity. Although lots of studies on EPs behavior in the aquatic environment are currently available in literature, an urgent requirement exists to complete toxicological studies and develop and implement efficient and ecological methods for their removal. This paper raises some relevant problems related to water environment pollution with EPs, the risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(95 citation statements)
references
References 137 publications
0
59
0
Order By: Relevance
“…In this research, two salt solutions were used: sodium chloride and magnesium chloride. To determinate the selectivity of the different membranes, the rejection coefficient was established using Equation (1).…”
Section: Selectivity and Performance Of Different Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, two salt solutions were used: sodium chloride and magnesium chloride. To determinate the selectivity of the different membranes, the rejection coefficient was established using Equation (1).…”
Section: Selectivity and Performance Of Different Membranesmentioning
confidence: 99%
“…Among these substances, there are compounds that are difficult to degrade due to their complex structure, which makes them stable and, consequently, poorly biodegradable. These compounds are called emerging pollutants [1].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Emerging pollutants groups and their major compounds [9][10][11] (Reprinted by permission). Water resources quality has deteriorated due to contamination caused by urbanization, rapid population growth, agricultural activities, and industrial development [12].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals, microbial pollutants, priority contaminants, and nutrients are the most commonly studied aspects of water quality. Nonetheless, recent research [11,13] revealed the presence of organic pollutants that have a significant impact on water parameters. The main issue with EPs is a lack of understanding about their long-term effects on aquatic life, the environment, and human health.…”
Section: Introductionmentioning
confidence: 99%
“…A review on emerging pollutants (EPs), sources for aquatic environment (e.g., wastewater treatment plants) and major impacts on biota and human health is reported by Vasilachi and co-authors [9]. The paper raises some relevant problems related to water environment pollution with EPs (e.g., UV filters), the risks they can generate for aquatic life and humans and opportunities to reduce the effects of pollution by their removal.…”
mentioning
confidence: 99%